Design and evaluation of a personal robot playing a self-management education game with children with diabetes type 1. Issue 106 (October 2017) - Henkemans, Olivier A. Blanson; Bierman, Bert P.B.; Janssen, Joris; Looije, Rosemarijn; Neerincx, Mark A.; van Dooren, Marierose M.M.; de Vries, Jitske L.E.; van der Burg, Gert Jan; Huisman, Sasja D.
Highlights: A personal robot, providing DSME to children with diabetes, is examined. Personalised robot behaviour is derived from SDT strategies. Personalised robot behaviour contributes to pleasure and motivation. Playing DSME games contributes to diabetes self-management knowledge. A coding scheme for child-robot interaction observations is developed. Abstract: Objective: To assess the effects of a personal robot, providing diabetes self-management education in a clinical setting on the pleasure, engagement and motivation to play a diabetes quiz of children (7–12) with type 1 diabetes mellitus (T1DM), and on their acquisition of knowledge about their illness. Methods: Children with T1DM ( N  = 27) participated in a randomized controlled trial (RCT) in which they played a diabetes mellitus self-management education (DMSE) game, namely a diabetes quiz, with a personal or neutral robot on three occasions at the clinic, or were allocated to a control group (care as usual). Personalised robot behaviour was based on the self-determination theory (SDT), focusing on the children's needs for competence, relatedness and autonomy. The SDT determinants pleasure, motivation and diabetes knowledge were measured. Child-robot interaction was observed, including level of engagement. Results: Results showed an increase in diabetes knowledge in children allocated to the robot groups and not in those allocated to the control group ( P  = .001). After three sessions, children working with the personal robot scored higher for determinants of SDT than children with the neutral robot ( P  = .02). They also found the robot to be more pleasurable ( P  = .04), they answered more quiz questions correctly ( P  = .02), and were more motivated to play a fourth time ( P  = .03). The analysis of audio/video recordings showed that in regard to engagement, children with the personal robot were more attentive to the robot, more social, and more positive ( P  < .05). Conclusion: The study showed how a personal robot that plays DMSE games and applies STD based strategies (i.e., provides constructive feedback, acknowledges feelings and moods, encourages competition and builds a rapport) can help to improve health literacy in children in an pleasurable, engaging and motivating way. Using a robot in health care could contribute to self-management in children with a chronic disease and help them to cope with their illness.